THE INFLUENCE OF WORKLOAD, WORK DISCIPLINE, AND WORK ENVIRONMENT ON ORGANIZATIONAL COMMITMENT AND EMPLOYEE PERFORMANCE AT THE KESBANGPOL AGENCY OF SOUTH SULAWESI PROVINCE - Siahaya, Aghnesia Carolina (Scientium Management Review, 2022)
The performance of an organization is inseparable from the achievement of the performance of the employees in it. This study aims to analyze the effect of workload, work discipline, and work environment on organizational commitment and employee performance at the Kesbangpol Agency of South Sulawesi Province, both directly and indirectly. This research is a quantitative research which is research based on the philosophy of positivism, used to examine a particular population or sample. The type of analysis in this study is path analysis using SPSS software to process the data resulting from the questionnaire distribution. The results of the study found that workload has a positive but not significant effect on organizational commitment, work discipline has a positive and significant effect on organizational commitment, work environment has a positive and significant influence on organizational commitment, workload has a positive and significant effect on employee performance, work discipline has a positive and significant effect on employee performance, the work environment has a positive but not significant effect on employee performance, organizational commitment has a positive and significant effect on employee performance, organizational commitment cannot mediate workload on employee performance, organizational commitment can mediate work discipline on performance employees positively and significantly, organizational commitment can mediate the work environment on employee performance in a positive and significant manner at the Kesbangpol Agency of South Sulawesi Province